Anatomía de la lámina foliar del género Trisetum (Gramineae: Pooideae) en México - Hernandez Torres, Ismael; Engleman, E. Mark (Instituto de Ecología, A.C., 1995)
Leaf anatomy in transverse section and abaxial epidermis for twelve species of Trisetum Pers. present in Mexico is described. Elongate mesophyll cells with undulated walls were observed in nine species. The epidermis costal zone of all species, except T. filifolium, showed short silica and cork cells frequently arranged in rows. Those short cells appeared solitary or in pairs in the intercostal zone of only four species. Solitary, elongate silica bodies undulated in outline were found in costal zone of all species.